2013
DOI: 10.1097/yct.0b013e318290f9e7
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Propofol to Prevent Fetal Deceleration During Electroconvulsive Therapy Treatment

Abstract: Electroconvulsive therapy has been demonstrated to be relatively safe during pregnancy for both the mother and the fetus. One risk to the fetus is cardiac deceleration during the grand mal seizure. We present a case of a young woman in her second trimester of pregnancy with bipolar depression. She had a prolonged seizure on her second electroconvulsive therapy treatment, which led to transient fetal bradycardia that self-corrected as preparations were underway for an emergency cesarean delivery. A change of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…General adverse effects like confusion, memory loss, muscle soreness and headache can occur post-ECT in any patient and, in pregnant women, these seem to become worse with continuing treatment [65,66]. Fetal bradyarrhythmia is the most common problem in the fetus caused by ECT [ A change of anesthetic agent from methohexital to propofol attenuated the seizure duration resulting in the elimination of further events of fetal cardiac deceleration and a successful outcome for both mother and fetus [81] Gahr et al to rTMS [82] Salzbrenner et al [85] O'Reardon et al Mother: cesarean delivery Fetus: no complications ECT was effective and safe for treating severe major depression during pregnancy [86] Pesiridou et al ECT during the third trimester of pregnancy may be delayed. Patients and treatment team need to be aware of this possibility, particularly when ECT is conducted on an outpatient basis [87] Ghanizadeh et al Ceccaldi et al [90] Pinette et al ECT is effective and safe [94] DeBattista et al Fukuchi et al Inhalation anesthesia is beneficial for ECT in the last stage of pregnancy to reduce uterine contractions caused by potential uterine relaxation effect of anesthetics [97] Bhatia et al ECT during pregnancy improves maternal condition and does not adversely affect fetal wellbeing [102] Sherer et al Mother: no complications Fetus: no complications ECT was highly effective and careful monitoring of both the mother and the fetus demonstrated that this was a safe procedure [103] Griffiths et al Transient fetal heart rate decreases probably result mainly from hypoxia [68].…”
Section: Discussionmentioning
confidence: 99%
“…General adverse effects like confusion, memory loss, muscle soreness and headache can occur post-ECT in any patient and, in pregnant women, these seem to become worse with continuing treatment [65,66]. Fetal bradyarrhythmia is the most common problem in the fetus caused by ECT [ A change of anesthetic agent from methohexital to propofol attenuated the seizure duration resulting in the elimination of further events of fetal cardiac deceleration and a successful outcome for both mother and fetus [81] Gahr et al to rTMS [82] Salzbrenner et al [85] O'Reardon et al Mother: cesarean delivery Fetus: no complications ECT was effective and safe for treating severe major depression during pregnancy [86] Pesiridou et al ECT during the third trimester of pregnancy may be delayed. Patients and treatment team need to be aware of this possibility, particularly when ECT is conducted on an outpatient basis [87] Ghanizadeh et al Ceccaldi et al [90] Pinette et al ECT is effective and safe [94] DeBattista et al Fukuchi et al Inhalation anesthesia is beneficial for ECT in the last stage of pregnancy to reduce uterine contractions caused by potential uterine relaxation effect of anesthetics [97] Bhatia et al ECT during pregnancy improves maternal condition and does not adversely affect fetal wellbeing [102] Sherer et al Mother: no complications Fetus: no complications ECT was highly effective and careful monitoring of both the mother and the fetus demonstrated that this was a safe procedure [103] Griffiths et al Transient fetal heart rate decreases probably result mainly from hypoxia [68].…”
Section: Discussionmentioning
confidence: 99%
“…However, given that these data are based on selectively reported cases, with no control population, and very mixed standards of reporting in publications from 1942 to 2013, it is unclear what weight to place on these findings. Note that it is reported that the risk of fetal bradycardia may be lower with propofol rather than methohexital (De Asis et al, 2013).…”
Section: Benefits and Harms Associated With Individual Medicationsmentioning
confidence: 99%
“…Note that it is reported that the risk of fetal bradycardia may be lower with propofol rather than methohexital (De Asis et al, 2013).…”
Section: Ect In the Perinatal Periodmentioning
confidence: 99%
“…Moreover, although methohexital and succinylcholine were initially used for anesthetic induction, the drugs were replaced with propofol since fetal bradycardia developed following fetal deceleration as a result of prolonged seizures. The authors also noted that the duration of seizures was shorter with propofol and the fetus was protected in a stable state [15]. Both recent reports and the data from our clinical practice indicate that 1 mg/kg propofol is often administered for anesthetic induction in ECT application.…”
Section: Discussionmentioning
confidence: 99%